SURVEY RESEARCH ON KANJI LEARNING STRATEGIES OF JAPANESE LEARNING STUDENTS - Kim Tuyen, Than Thi (VNU Journal of Foreign Studies, 2019)
One of the hardest issues in learning Japanese is learning Kanji. In Japanese studies, there are more than 7000 words made up of over 2500 kanji characters. In addition, to learn Kanji words, students also need to remember all the three factors: writing, reading (‘on’ reading and ‘kun’ reading), and meaning. Therefore, Japanese learners often use multiple strategies to memorize Kanji. The survey was conducted among 123 third-year students of the Faculty of Japanese Language and Culture, University of Foreign Languages, Vietnam National University, Hanoi to find out which methods are frequently used. In addition, this research further identifies the difference in study habits of male and female students, as well as of students with different Japanese proficiency levels (N1, N2, and N3). The research also asks students to list additional learning strategies besides the ones that were originally included in the survey. The most frequently used strategies are ‘Looking up unknown Kanji in a dictionary’, ‘Write over and over again’ and many of the most commonly used strategies are related to Sino-Vietnamese vocabulary. Gender differences in study habits were found where male students mostly use visualization, while female students tend to learn by using Kanji in writing and character association. Students often use Sino-Vietnamese vocabulary when they start learning Kanji. However, the higher students’ levels are, the less Sino-Vietnamese words are used.